Pendampingan Pembuatan Media Pembelajaran Geografi Berbasis Google Site Bagi Guru Geografi Kota Banjarmasin - Karunia Puji Hastuti; Nevy Farista Aristin; Deasy Arisanty; Sidharta Adyatma; Danti Alma Viandra (Jurnal Pemberdayaan Masyarakat, 2025)
This community service program aimed to improve the capacity of high school geography teachers in Banjarmasin to develop digital-based learning media using Google Sites. The program responded to the limited use of digital tools in geography education, particularly in integrating spatial data, interactive maps, and local content. With the growing need for innovative, contextual, and accessible learning, the program involved stages of preparation, training, simulation, and mentoring. Google Sites emerged as a free, easy-to-use alternative solution. Google Sites offers the advantage of being an easily accessible, flexible, and free platform, making it an ideal choice for geography learning in the context of high school teaching in Banjarmasin City. A total of 30 geography teachers participated. The results showed improved teacher skills in designing integrated instructional websites. This highlights the importance of continuous training and technical support to enhance digital competencies among educators. This program is expected to serve as a model for enhancing the pedagogical competence of high school geography teachers in addressing the challenges of 21st-century learning. In addition, the results of this activity have implications for improving the quality of high school geography learning in Banjaramsin City, particularly through the integration of technology during learning activities.